Peer Counseling as a Strategy for Developing Critical Thinking Skills Among Adolescents in Islamic Educational Settings - Alfiane Suci Setyasri; Tsabita Fathin Daniya; Galuh Andina Putri (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2026)
The era of information disruption and massive exposure to social media trigger cognitive vulnerability and Fear of Missing Out (FoMO) among adolescents, requiring educational institutions to proactively equip students with critical thinking skills. This study aims to explore the role of peer counseling as a strategy for developing adolescent critical thinking in an Islamic educational environment. Using a qualitative approach with a case study design at SMA Future Gate Putri Boarding Bekasi, data were collected through non-participatory observation, in-depth interviews with counselors and counselees, and document studies. The results indicate that peer counseling effectively functions as cognitive scaffolding for students. Through the application of the Plus-Minus-Implication (PMI) method and the principle of Tabayyun (verification), this intervention facilitates emotional regulation through psychological equality, which is a prerequisite for achieving rational thinking. The program successfully transformed students’ reactive attitudes into proactive ones, improved cognitive independence, fostered assertiveness, and reduced dependence on digital trends. In conclusion, peer counseling has proven to be a comprehensive method that successfully integrates 21st-century skills with Islamic character values to respond to the challenges of the disruption era.